Cultural Heritage-Based Tourism Business Prospects At The Siak Palace, Siak Sri Indrapura Regency - Ibrahim, Mariaty; Augustin, Jeneva; Fadli, Mashur (Publisher Cv. Inara, 2025)
The tourism development strategy is an effort made by the Tourism Office to develop existing tourism to become an attraction for tourists, but the development of tourism at the Siak Palace has not been optimal, resulting in a decline in the number of tourist visits to the Siak Palace in Siak Sri Indrapura Regency. The purpose of this study is to determine the prospects for tourism development at the Tourism Office of Siak Sri Indrapura Regency, and to determine the factors that influence the prospects for developing Siak Palace tourism in Siak Sri Indrapura Regency. In this study, the method used is a qualitative approach that can understand the research in depth with descriptive analysis methods. In this qualitative study, data were obtained from literature studies and also field studies, such as observations, interviews, and documents obtained from related agencies or using other media that can be used as research data. The results obtained from the study are in the first process, the Tourism Office, Siak Regency, has established a vision and mission, namely, by developing tourism destinations. In this case, specifically to develop the Siak Palace tourist attraction. Then analyze the internal and external environment to determine the strengths, weaknesses, opportunities, and threats in the development of the Siak Palace tourist attraction. In this case, the researcher used a SWOT analysis. In addition, the researcher also analyzed the long-term goals of the Tourism Office and how to achieve the mission for the next five years. Then, they examined whether the strategies that had been made were successful or not by looking at the annual targets that had been set by the Tourism Office, Siak Regency. Then, the policies are used to achieve the annual targets. In this case, the policies were in the form of guidelines, rules, and procedures established to support the desired goals. The conclusion is that the Tourism Office, Siak Regency, has carried out the strategic planning process well. Every aspect of the strategic planning has been carried out optimally and also by the established rules. Although the strategic planning that has been made has been running well, the process has still not been able to develop the Siak Palace tourist attraction optimally because it still requires more action than what has been stated in the Tourism Office's project planning, Siak Regency.